2022
DOI: 10.1002/jper.21-0623
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 RNA in dental biofilms: Supragingival and subgingival findings from inpatients in a COVID‐19 intensive care unit

Abstract: Background Saliva, salivary glands, gingival crevicular fluid, and supragingival biofilms may harbor SARS‐CoV‐2 RNA. This observational study aimed to investigate the presence and load of SARS‐CoV‐2 RNA in supragingival, and subgingival biofilms obtained from intensive care unit (ICU) patients. Methods A convenience sample, composed of 52 COVID‐19+ participants (48.6 ± 14.8 years, 26.9% females), were evaluated for pre‐existing comorbidities, number of teeth, and period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…In our study, periodontal examination was performed during the infection and the diagnosis of periodontitis was based on PD, CAL, and tooth loss; moreover, a matched control group was included. In contrast, some studies did not perform clinical periodontal examination [ 8 , 9 ], did not include a control group [ 12 , 35 ], and only evaluated patients after the infection [ 10 ]. Multivariate analysis showed that even after the removal of confounders, periodontitis persisted as a significant factor regarding the need of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, periodontal examination was performed during the infection and the diagnosis of periodontitis was based on PD, CAL, and tooth loss; moreover, a matched control group was included. In contrast, some studies did not perform clinical periodontal examination [ 8 , 9 ], did not include a control group [ 12 , 35 ], and only evaluated patients after the infection [ 10 ]. Multivariate analysis showed that even after the removal of confounders, periodontitis persisted as a significant factor regarding the need of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of cases that SARS-CoV-2 co-infects with other pathogens include venerable age, glucocorticoid therapy, immunocompromised state, long-term antibiotic use history, diabetes, cardiovascular comorbidities, intensive care unit attending, ventilation treatment, prolonged hospitalization time, and exacerbation of symptoms ( Bao et al., 2020 ; Blasco et al., 2020 ; Contou et al., 2020 ; Wang et al., 2020a ; Alhumaid et al., 2021 ; He et al., 2021 ; Yasmin et al., 2021 ; Gomes et al., 2022 ; Hedberg et al., 2022 ; Ortega-Pena et al., 2022 ; Rouze et al., 2022 ; SeyedAlinaghi et al., 2022 ; Shetty et al., 2022 ). Bacterial pathogens generally isolated cover M. pneumoniae , P. aeruginosa , H. influenzae , K. pneumoniae and S. pneumoniae ( Lansbury et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abundant cases of SARS-CoV-2 co-infection with other microorganisms have been reported, which were associated with venerable age, immunosuppression, cardiovascular disease, diabetes, intensive care unit attending, mechanical ventilation treatment, long-term antibiotic use, glucocorticoid therapy, prolonged hospitalization, exacerbation of symptoms, and poor prognosis ( Bao et al., 2020 ; Blasco et al., 2020 ; Contou et al., 2020 ; Wang et al., 2020a ; Alhumaid et al., 2021 ; He et al., 2021 ; Yasmin et al., 2021 ; Gomes et al., 2022 ; Hedberg et al., 2022 ; Ortega-Pena et al., 2022 ; Rouze et al., 2022 ; SeyedAlinaghi et al., 2022 ; Shetty et al., 2022 ). M. pneumoniae , P. aeruginosa , H. influenzae , and K. pneumoniae are bacterial co-pathogens usually detected ( Lansbury et al., 2020 ).…”
Section: The Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 can be found in many sites in the oral cavity, such as mucosal cells and tissues, saliva, supra and subgingival biofilms, and gingival crevicular fluid. 8 ),( 9 ),( 10 As the virus has an airborne transmission, dental care had to undergo several adaptations to avoid its dissemination. 11 For biosafety reasons, Dental Schools were closed for patients for several months.…”
Section: Introductionmentioning
confidence: 99%